Bioinformational diplomacy: Global health emergencies, data sharing and sequential life. (September 2021) - Elbe, Stefan
Global health emergencies – like COVID-19 – pose major and recurring threats in the 21st century. Now societies can be better protected against such harrowing outbreaks by analysing the detailed genetic sequence data of new pathogens. Why, then, is this valuable epistemic resource frequently withheld by stakeholders – hamstringing the international response and potentially putting lives at risk? This article initiates the social scientific study of bioinformational diplomacy, that is, the emerging field of tensions, sensitivities, practices and enabling instruments surrounding the timely international exchange of bioinformation about global health emergencies. The article genealogically locates this nascent field at the intersection of molecularised life, informationalised biology and securitised health. It investigates the deeper political, economic and scientific problematisations that are engendering this burgeoning field. It finally analyses the emergent international instruments developed by governments, scientists and industry to facilitate more rapid global sharing of bioinformation through novel practices of data passporting. Overall, the in-depth study of bioinformational diplomacy reveals just how deeply, and even constitutively, international relations are entangled with the life sciences – by carefully tracing how laboratory practices of sequencing life at molecular scale also end up recontouring the play of sovereignty, power and security in international relations.